Teacher perspectives on information skills for learning in the secondary school instructional programme - Leung, Shirley Lai Ying. (2009)
The need for pupils to be equipped with information skills so that they leave school as an information literate individual able to meet the demands of a new workplace is recognised as a necessity in today's world. Teachers are seen as the key determining factor for pupils to be well-equipped with information skills.